Differential sensitivity of acute myeloid leukemia cells to daunorubicin depends on P2X7A versus P2X7B receptor expression - Pegoraro, Anna; Orioli, Elisa; De Marchi, Elena; Salvestrini, Valentina; Milani, Asia; Di Virgilio, Francesco; Curti, Antonio; Adinolfi, Elena (Cell death & disease, 2020)
Acute myeloid leukemia (AML) is a common adult leukemia often arising from a preexistent myelodysplastic syndrome (MDS). High mortality rates of AML are caused by relapse and chemoresistance; therefore, we analyzed the role of P2X7 receptor (P2X7R) splice variants A and B in AML progression and response to chemotherapy. The expression of P2X7RA and P2X7RB was investigated in samples obtained from MDS and AML untreated subjects or AML patients in relapse or remission after chemotherapy. Both P2X7RA and P2X7RB were overexpressed in AML versus MDS suggesting a disease-promoting function. However, in relapsing patients, P2X7RA was downmodulated, while P2X7RB was upmodulated. Treatment with daunorubicin (DNR), one of the main chemotherapeutics for AML, upregulated P2X7RB expression while reducing P2X7RA mRNA in AML blasts. Interestingly, DNR administration also caused ATP release from AML blasts suggesting that, following chemotherapy, activation of the receptor isoforms via their agonist will be responsible for the differential survival of blasts overexpressing P2X7RA versus P2X7RB. Indeed, AML blasts expressing high levels of P2X7RA were more prone to cell death if exposed to DNR, while those overexpressing P2X7RB were more vital and even protected against DNR toxicity. These data were reproducible also in HEK-293 cells separately expressing P2X7RA and B. P2X7RA facilitation of DNR toxicity was in part due to increased uptake of the drug inside the cell that was lost upon P2X7RB expression. Finally, in an AML xenograft model administration of DNR or the P2X7R antagonist, AZ10606120 significantly reduced leukemic growth and coadministration of the drugs proved more efficacious than single treatment as it reduced both P2X7RA and P2X7RB levels and downmodulated c-myc oncogene. Taken together, our data suggest P2X7RA and P2X7RB as potential prognostic markers for AML and P2X7RB as a therapeutic target to overcome chemoresistance in AML relapsing patients.